Insulin resistance in moderate to severe acne vulgaris - Monika Singh; Dikshant Shri (Wolters Kluwer Medknow Publications, 2022)
Introduction: Acne vulgaris is a chronic inflammatory disease of the pilosebaceous unit usually affects adolescents. It is seen on the face, neck, trunk and arms. The main pathogenic factors of acne are high sebaceous gland secretion, follicular hyper proliferation, high androgen effects, propionibacterium acnes colonization and inflammation. Objectives: To determine the presence of insulin resistance in moderate to very severe acne vulgaris. Material and Methods: One hundred sixty subjects were enrolled in the study consisting of 80 patients with moderate to very severe acne vulgaris and 80 age and sex-matched controls without acne. Fasting serum insulin and glucose levels were measured and insulin resistance was calculated by Homeostasis Model Assessment- Insulin Resistance (HOMA-IR) Index. The values were compared with the healthy control group. Results: Significant difference was observed in HOMA values and fasting insulin among the two groups (P < 0.001). The levels were significantly higher in the patient group than in the control group, whereas no significant difference was present in fasting glucose levels between the two group. Conclusions: In conclusion, insulin resistance was seen in majority of patients with acne. These results can add to the evidence regarding a potential association between metabolic dysregulation and acne.